HUBUNGAN ANTARA BEBAN KERJA MENTAL DAN SHIFT KERJA TERHADAP STRES KERJA PADA PEKERJA CENTRAL CONTROL ROOM (Studi Kasus Pada PT. PJB Unit Pembangkit Paiton Probolinggo) - Amirul Hasan; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Job stress is a form of self adaptation that influenced by individual characteristic and psychological process as the response of environment changes. Factors that influenced job stress are workload, work environment, work responsibility, or as a result of failed-adaptation with the work-mates or the work-tasks. The aim of this research is to analyze the corrrelation of workload mentality and shift of work towarads job stress in PT.PJB. UP Paiton. The research method used was analytical descriptive with cross-sectional design. Dependent variable of this research is job stress and independent variables are workload mentality and shift of work. Population of this study was all 32 CCR workers and this research used all population as research subject. Data were collected by filled the research instruments which was GHQ-12 and NASA-TLX. Data analysis used chi-square and mann-whitney test. The result showed there was a correlation between workload mentality (p = 0,029) and shift of work (p = 0,022) towards job stress of workers. In order to decrease work stress, the company should provide education about job stress, the causes of stress and how to control it, and company should allow workers to do stretching between work hours.